The Historical and Olympic Heritage of Sochi - Oleg Kozinsky (Проект Байкал, 2019)
The article reviews the formation of the Sochi resort, the peculiarities of urban development of the Sochi resort agglomeration. It points out the historical role of architecture experts, academicians of the USSR Academy of Architecture in the formation of its architectural image. The article touches upon the problems of degradation of the historical environment and its safety in the context of excessive urbanization and imperfection of legislative regulation of the development of the resort with peculiar natural and climate conditions. The article poses a question about the object of protection of the historical settlement and its boundaries, as well as underlines the necessity for a complex scientific-design and regulatory approach to the achievement of the goals set in the Strategy of Social-Eco- nomic Development of the Krasnodar Region for the resort city of Sochi.